Not all that glitters is gold: Glitter causes acute toxicity to nauplii of Artemia sp. - Abessa, Denis Moledo de Souza [UNESP] (2024)
Glitter has been reported as a relevant pollutant, as it is widely used in cosmetic and textile products and craftwork, and often associated with domestic sewage. The particular glitter is composed of thin layers of plastic and metal. This study assessed the acute toxicity of glitter dispersions in the brine shrimp Artemia sp. Nauplii of Artemia sp. that were exposed to glitter dispersions (0.01, 0.1, 1, 10, and 100 mg/L), obtained by diluting a stock solution in seawater; the control consisted of filtered seawater only. Three replicates were used per treatment and consisted of glass tubes filled with 10 mL of the test solution, and ten nauplii aging over 48 h. After 48 h, the survivors were counted and examined under a microscope. The mean size of glitter particles was 3.94 (±0.98) µm; approximately 44 % of particles were in the range of very fine sand, and 27 % coarse silt. Significant lethal effects (p < 0.05) occurred from 0.1 mg/L (Lowest Observed Effect Concentration-LOEC); the lethal concentration to 50 % organisms (LC50-48h) was 0.350 (0.348-0.351) mg/L. The exposed organisms also exhibited patches in their digestive tracts, and particles were stranded in their appendices. The results indicate the toxic potential of glitter to brine shrimp. This investigation indicates the need for further studies on the toxicity of glitter to marine invertebrates.